Visual feedback based on expired CO2 as a therapy method for respiratory disturbances in stuttering - Stankiewicz, B.; Adamczyk, B.; Zieliński, K.; Darowski, M. (Archives of Acoustics, 2006)
A new CO2-based visual feedback therapy method (VF) for respiratory disturbances in stuttering was preliminarily assessed. Sound and expired CO2 signals were registered in 12 stutterers and 12 fluent speakers while speaking without and with VF to control breathing as well as during rest respiration, before each utterance. In stutterers, the end-tidal CO2 (ETCO2), the area under CO2/a time curve (SCO2), and the average emission of CO2 (ECO2 = SCO2/tbreath_cycle) for the CO2 peaks connected with the phrases containing tonic errors (with reference to rest respiration) were higher than those connected with fluent phrases (p